Dealbreaker - Beckett, L. X. (Tor, 2021)
"Ruby Whiting has done the impossible. She has proved that humanity deserves a seat at the galactic table. Well, at least a shot at a seat. Having convinced the galactic governing body that mankind deserves a chance at fixing their own problems, Ruby has done her part to launch the planet into a new golden age of scientific discovery and technological revolution. However, there are still those in the galactic community that think that humanity is too poisonous, too greedy, to be allowed in, and they will stop at nothing to sabotage a species determined to pull itself up"--